2000
DOI: 10.1063/1.126410
|View full text |Cite
|
Sign up to set email alerts
|

Wave function-dependent mobility and suppression of interface roughness scattering in a strained SiGe p-channel field-effect structure

Abstract: The 4 K Hall mobility has been measured in a top-gated, inverted, modulation-doped Si/Si0.8Ge0.2 structure having a Si:B doping layer beneath the alloy. From comparisons with theoretical calculations, we argue that, unlike an ordinary enhancement-mode SiGe p-channel metal–oxide–semiconductor structure, this configuration leads to a decrease of interface roughness scattering with increasing sheet carrier density. We also speculate on the nature of the interface charge observed in these structures at low tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 24 publications
(20 reference statements)
0
13
0
Order By: Relevance
“…[12] have shown that a corrugated interface may also lead to scattering from piezoelectric charges and suggest that this may be the reason for the postulation [18] of an apparent high interface charge density in p-Si/SiGe heterostructures [11]. In bulk Si or Ge, no piezoelectricity can be observed due to cubic crystal symmetry.…”
Section: Resultsmentioning
confidence: 95%
“…[12] have shown that a corrugated interface may also lead to scattering from piezoelectric charges and suggest that this may be the reason for the postulation [18] of an apparent high interface charge density in p-Si/SiGe heterostructures [11]. In bulk Si or Ge, no piezoelectricity can be observed due to cubic crystal symmetry.…”
Section: Resultsmentioning
confidence: 95%
“…In the previous studies [5], it has always been assumed that the deformation potential experienced by the holes in the valence band is identical to that experienced by electrons in the conduction band [17] with a different coupling constant Ξ . This assumption is, in fact, invalid.…”
Section: Original Papermentioning
confidence: 99%
“…First, the potential barrier at the HS's interface is always assumed to be infinite [2,3], although it is small, thus changes the transport properties of the HS [3,4]. Next, deformation potential scattering limiting the 2D hole mobility is always based on the idea that the holes and the electrons undergo the same deformation potential [5]. This assumption was indicated [4] to be invalid, and the properly derived deformation scattering was found [4] to strongly limit the 2D hole mobility.…”
Section: Introductionmentioning
confidence: 97%
“…3b). This might be attributed to taking account the ground state wave function in our proposed model in this work that affects the short channel devices [24].…”
Section: From Eqs (4 4a-4c) and The Threshold Condition One Hasmentioning
confidence: 99%